Cara Bagi Hasil Dalam Peminatan Masyarakat Untuk Melakukan Investasi Dalam Kajian Ekonomi Syariah - Ulfatul Khasanah; Ayu Maretta Maharani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
At that time Indonesia was on the verge of economic collapse, almost all economic sectors experienced negative growth. Where the construction sector is the sector that experienced the largest negative growth, namely minus 40% due to very high interest rates, a decrease in purchasing power and a very large debt burden. The trade and services sector experienced a contraction of minus 21%, the manufacturing industry sector decreased by 19%. All resulted from the implications of the monetary crisis that rocked Indonesia. This is because people's purchasing power is still minimal. Therefore, one of the efforts to revive the economy includes profit sharing. The profit sharing system implemented in sharia banking is divided into two systems, namely; First. Profit Sharing is a profit sharing system that is based on the net results of income received from business collaboration, after deductions have been made for costs incurred during the business process. Second. Revenue Sharing is a profit sharing system that is based on the total of all income received before deducting the costs incurred to obtain that income.